Criminal Acts Revenge Pornography In Terms Of Indonesian Criminal Law - Dwita Rahmawati; Ifahda Pratama Hapsari; Hardian Iskandar (IHSA Institute, 2022)
Crimes in the form of content containing immorality or sex are increasingly occurring in online networks, one of which is revenge pornography, commonly known as